Proteome Analyses Reveal Positive Association of COL2A1, MPO, TYMS, and IGFBP5 with Canine Mammary Gland Malignancy - Wu, Chih‐Ching; Chang, Shih‐Chieh; Zeng, Guang‐You; Chu, Hao‐Wei; Huang, Yenlin; Liu, Hao‐Ping (Proteomics. Clinical applications, 2019)
Purpose To identify aberrantly expressed proteins contributing to pathogenesis of canine mammary tumors (CMTs) which are the most prevalent neoplasms in female dogs and include different types. Experimental design Frozen tissue specimens of normal mammary gland (n = 7), lobular hyperplasia (n = 6), simple carcinoma (n = 6), and complex carcinoma (n = 6) are collected from 11 CMT cases. Tissue homogenates are comparatively analyzed by the isobaric tags for relative and absolute quantification (iTRAQ) combined with LC‐MS/MS to identify proteins differentially expressed in different‐type CMT tissues. Results Among 3795 proteins identified and quantified among all groups, 133, 127, and 98 proteins are particularly overexpressed in simple carcinoma, complex carcinoma, and both types, respectively, compared with normal and hyperplastic tissues. Moreover, collagen type II alpha 1 chain (COL2A), myeloperoxidase (MPO), thymidylate synthetase (TYMS), and insulin‐like growth factor‐binding protein 5 (IGFBP5) are validated to be highly expressed in different‐type CMT tissues using immunoblotting and immunohistochemistry. Notably, COL2A1 and IGFBP5 levels are correlated with clinical stages. Conclusions and clinical relevance COL2A1, MPO, TYMS, and IGFBP5 protein levels are positively associated with CMT development. Data expedite further investigations to improve treatment regimens for CMT.